The EU’s Regulation on the Sustainable Management of External Fishing Fleets: International and European Law Perspectives - Guggisberg, S.A. (Martinus Nijhoff Publishers, 2019)
The European Union’s (EU) new Regulation on the sustainable management of external fishing fleets strengthens the framework under which authorisations are granted to EU vessels desiring to fish outside of EU waters. It applies to all such fishing activities, conditions the granting of authorisations on sustainability criteria, and provides a level of institutional control on Member States’ actions, as well as some transparency. It also covers poorly monitored practices, such as reflagging and chartering. However, there have been some missed opportunities, in particular with regard to unregulated high seas fishing and the public accessibility of data on beneficial ownership. More generally, the impact on sustainability of the EU’s stricter measures will depend, in the highly inter-connected world of fisheries, on whether other States also embrace such good governance principles.
Keywords: fisheries; European Union; Common Fisheries Policy; external fishing fleet; distant-water fishing; SDG 14 - Life Below Water; SDG 16 - Peace, Justice and Strong Institutions